Effect of Strategic Analysis and Strategy Implementation on Service Quality of a Popular Telecommunication Company in Nigeria - C.N., Aguoru; S., Orsaah; M., Umogbai (International Journal of Scientific Research and Management (IJSRM), 2018)
This study critically examined the effect of strategic planning and strategy implementation on the service quality of a popular telecommunication network provider in Nigeria. A survey research design was adopted through the use of structured questionnaires randomly administered to some MTN staff in the north central axis. Hypotheses were formulated followed by data validation, reliability and analysis using appropriate descriptive and inferential statistics. The Kaiser- Meyer- Olkin (KMO) test which measured the sample adequacy was .656 while the Bartlett's Test of Sphericity was significant (X2= 84.362, p= .000). The overall result was reliable with the Cronbach’s Alpha values greater than 0.70 for each variable measured. Result showed that most of the workers (about 54%) had 2-4years working experience with the organization while the longest length of service was approximately 12% in the work force. All the parameters measured were above the minimum agreeable benchmark of 3.5. The environment of the business affects its performance with a mean value of 4.12. There are enough resources to help the organization achieve its goal (4.3). The analysis of resources in the organization has helped improve the quality of services rendered (4.25).  The adoption of strategic analysis by MTN helped in improving the service quality of company. Strategic analysis and strategy implementation each had significant relationship with service quality (F=25.48, p=0.000, R2= 53.5). All the seven indicators of service quality employed indicated high results. The organization is reliable with good assurance. Network quality recorded the highest mean (3.71). Other results such as competitive advantage and reliability (3.22) attested to the high service quality of the organization. With the average service quality of 3.09, the corporate planning of MTN is oriented towards retaining customers through the provision of high quality of its service.